Krankenhauskooperationsmodelle - Welsch, Thilo; Frankenberg, Moritz von; Simon, Thomas; Weitz, Jürgen; Büchler, Markus W. (Der Chirurg, 2012)
IntroductionIn the face of continuous medical progress on the one hand and the increasing cost pressure through the diagnosis-related groups (DRG) system with concomitant hospital privatization on the other, pioneering and economical models for modern and competent patient care are required.MethodsThe cooperation model of the surgical department of the Heidelberg University Hospital is based on patient selection according to the grade of disease complexity and has been successfully developed in Heidelberg since 2005. The long-term results on the basis of actual proceeds are presented.ResultsCooperation with the Salem Hospital chaired by the director of the University surgical department has been ongoing for 6 years. General visceral surgery cases with low complexity are treated at the secondary cooperation hospitals whereas complex oncological operations of the esophagus, liver, pancreas, rectum or multivisceral resections and transplantations are performed at the University hospital. Optimal utilization of the operative and infrastructural resources of both cooperation partners lead to an improvement in surgical training and proceeds. Likewise, another cooperation with the secondary hospital in Sinsheim, which started 2 years ago, has shown similar positive results. Clinical rotation for surgical residents and attending surgeons guarantee a complete and competent surgical training in the field of general surgery.ConclusionsThe long-term results indicate that the cooperation model functions to achieve an optimized treatment of patients and an economical win-win situation for all cooperation partners by differential utilization of the available resources in the hospital network.
Gesehen am 16.05.2019